Choice of Lowest Instrumented Vertebra (LIV) in Adolescent Idiopathic Scoliosis (AIS); Discordance in Stable Sagittal Vertebra and Coronal Last Touched Vertebra. (16th November 2020) - Menger, Richard P; Park, Paul; Konigsberg, Matthew; Marciano, Gerard; Lenke, Lawrence; Vitale, Michael
Abstract: INTRODUCTION: Traditionally, coronal plane considerations have been the primary driver in the selection of lower instrumented vertebra in patients with adolescent idiopathic scoliosis. More recent sagittal criteria have been applied to the decision. Here we quantify how these two criteria can result in discordant decisions for LIV. METHODS: Retrospective review was performed of consecutive patients undergoing fusion for AIS from 2016–2018. Inclusion criteria included < age 18 with a 1B, 1C, 2B, or 2C curve. SSV was defined as the most proximal vertebra touched by the posterior sacral vertical line (PSVL). Last touched vertebra (LTV) was defined as the last significantly touched vertebrae where the central sacral vertebral line (CSVL) was between the pedicles or touching the pedicle. Age, sex, classification, comorbidities, and coronal Cobb angles were noted. RESULTS: In this review of 40 consecutive patients with AIS, average age was 13.9 years and average coronal main thoracic curve was 53.7 degrees. In 35.0% (14/40), there was disagreement between the LIV based on the SSV compared with that based on the LTV, with an absolute mean discordance of 2.1 levels. 78.6% (11/14) of the time the SSV was more distal than the LTV. SSV was included within the fusion construct 87.5% (35/40) of the time. Average distance of the lower instrumented vertebra to the stable sagittal vertebra was 1.1 levels. CONCLUSION: The SSV and LTV suggest different levels for the lowest instrumented vertebra for 35.0% of the time with 87.5% of fusion constructs incorporating the SSV. Coronal and sagittal selection criteria show disagreement that can impact selection of the LIV. Further investigation is warranted to determine the impact on distal junctional kyphosis and failure.